Developing a National Trauma Research Action Plan: Results from the Neurotrauma Research Panel Delphi Survey. Issue 5 (6th May 2022) - Stein, Deborah M.; Braverman, Maxwell A.; Phuong, Jimmy; Shipper, Edward; Price, Michelle A.; Bixby, Pamela J.; Adelson, P. David; Ansel, Beth M.; Cifu, David X.; DeVine, John G.; Galvagno, Samuel M.; Gelb, Daniel E.; et al.
Abstract : "The National Trauma Research Action Plan (NTRAP) Neurotrauma Panel comprising interdisciplinary experts identified gaps in the neurotrauma literature, generated research questions, and prioritized those questions using a consensus-driven Delphi survey approach. #NatTrauma" Abstract : BACKGROUND: In 2016, the National Academies of Science, Engineering and Medicine called for the development of a National Trauma Research Action Plan. The Department of Defense funded the Coalition for National Trauma Research to generate a comprehensive research agenda spanning the continuum of trauma and burn care. Given the public health burden of injuries to the central nervous system, neurotrauma was one of 11 panels formed to address this recommendation with a gap analysis and generation of high-priority research questions. METHODS: We recruited interdisciplinary experts to identify gaps in the neurotrauma literature, generate research questions, and prioritize those questions using a consensus-driven Delphi survey approach. We conducted four Delphi rounds in which participants generated key research questions and then prioritized the importance of the questions on a 9-point Likert scale. Consensus was defined as 60% or greater of panelists agreeing on the priority category. We then coded research questions using an National Trauma Research Action Plan taxonomy of 118 research concepts, which were consistent across all 11 panels. RESULTS: Twenty-eight neurotrauma experts generated 675 research questions. Of these, 364 (53.9%) reached consensus, and 56 were determined to be high priority (15.4%), 303 were deemed to be medium priority (83.2%), and 5 were low priority (1.4%). The research topics were stratified into three groups—severe traumatic brain injury (TBI), mild TBI (mTBI), and spinal cord injury. The number of high-priority questions for each subtopic was 46 for severe TBI (19.7%), 3 for mTBI (4.3%) and 7 for SCI (11.7%). CONCLUSION: This Delphi gap analysis of neurotrauma research identified 56 high-priority research questions. There are clear areas of focus for severe TBI, mTBI, and spinal cord injury that will help guide investigators in future neurotrauma research. Funding agencies should consider these gaps when they prioritize future research. LEVEL OF EVIDENCE: Diagnostic Test or Criteria, Level IV. Abstract :